Brain reactions to the use of sensorized hand prosthesis in amputees. Issue 11 (19th September 2020) - Granata, Giuseppe; Di Iorio, Riccardo; Miraglia, Francesca; Caulo, Massimo; Iodice, Francesco; Vecchio, Fabrizio; Valle, Giacomo; Strauss, Ivo; D'anna, Edoardo; Iberite, Francesco; Lauretti, Liverana; Fernandez, Eduardo; et al.
Abstract: Objective: We investigated for the first time the presence of chronic changes in the functional organization of sensorimotor brain areas induced by prolonged training with a bidirectional hand prosthesis. Methods: A multimodal neurophysiological and neuroimaging evaluation of brain functional changes occurring during training in five consecutive amputees participating to experimental trials with robotic hands over a period of 10 years was carried out. In particular, modifications to the functional anatomy of sensorimotor brain areas under resting conditions were explored in order to check for eventual changes with respect to baseline. Results: Full evidence is provided to demonstrate brain functional changes, and some of them in both the hemispheres and others restricted to the hemisphere contralateral to the amputation/prosthetic hand. Conclusions: The study describes a unique experimental experience showing that brain reactions to the prolonged use of an artificial hand can be tracked for a tailored approach to a fully embedded artificial upper limb for future chronic uses in daily activities. Abstract : Recent technological advancements have allowed for a bidirectional connection of the prosthetic hand via intraneural electrodes in stump nerve trunks. No reports are available so far on modifications in brain function accompanying the use of a bidirectional hand prosthesis. We performed a multimodal neurophysiological and neuroimaging evaluation of brain functional changes occurring during training with a bidirectional hand prosthesis in five consecutive patients, and demonstrating brain functional changes related to the use of the prosthetic hand.